BRAIN NEURON REGENERATION IN POST-STROKE REHABILITATION TREATMENT USING GRAPE PEEL AND SEED EXTRACT (Vitis vinifera) IN INDUCING ERK1 / 2 PATHWAY - Lie, Zanella Yolanda; Tandiono, Meliantha; Pricillia, Lucy; Lukito, Astrid Nandikasari; Gasmara, Cakra Parindra (Malang Neurology Journal, 2016)
Background. Ischemic stroke can cause hypoxia in brain tissue and damage the neuron. The defense ability and plasticity is activated by ERK1/2 pathway. Grape peel and seed extract (Vitis vinifera can induce release neurotrophic factor that contribute in ERK1/2 pathway mechanism.Objective. To prove that grape peel and seed extract can regenerate neuron in anatomical and functional view.Methods. This research use true experimental design with sample in this research is 20 male 8-10 weeks old wistar strain rats which are induced stroke by internal and external carotid artery occlusion method.Results. The repairment is monitored from four parameters, namely cylinder test score, ladder rung walking test score, extensive infarct volume, and number of damaged neuron. Conclusion. The result is 50mg/KgBW is effective in repairing neuron. It is seen from the result of improvement in four parameters explained above.